2014
DOI: 10.1177/8755122513518497
|View full text |Cite
|
Sign up to set email alerts
|

The Scholarly Merit of Social Media Use Among Clinical Faculty

Abstract: Background: Social media (SoMe) platforms such as blogs, Twitter, and Facebook are increasingly becoming incorporated into education and scientific communities. In fields such as emergency medicine, clinicians have established communication channels through SoMe to engage in academic and clinical discussions for the purposes of professional growth. While the use of SoMe as an educational tool within the classroom has been previously described, its use as a professional tool has not been adequately investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One example of scholarly social media being considered in RPT evaluation is that of the Mayo Clinic – starting in early 2016, digital portfolios were allowed in evaluations for promotion ( Cabrera et al ., 2017). Cocchio & Awad (2014) reported that across medical, nursing, and pharmacy programs, deans have varying views regarding the value of social media in the evaluation of scholarly activity. 31% of these deans were of the opinion that high viewership of scholarly works increased academic merit, and 52% thought peer review of materials published online would also add value.…”
Section: Modern Approaches To Evaluating Research Outputmentioning
confidence: 99%
“…One example of scholarly social media being considered in RPT evaluation is that of the Mayo Clinic – starting in early 2016, digital portfolios were allowed in evaluations for promotion ( Cabrera et al ., 2017). Cocchio & Awad (2014) reported that across medical, nursing, and pharmacy programs, deans have varying views regarding the value of social media in the evaluation of scholarly activity. 31% of these deans were of the opinion that high viewership of scholarly works increased academic merit, and 52% thought peer review of materials published online would also add value.…”
Section: Modern Approaches To Evaluating Research Outputmentioning
confidence: 99%
“…The nursing education literature demonstrates social media's potential as a teaching and learning tool, although much of the focus has been on social media's use by nursing faculty for teaching at the undergraduate level. Teaching through social media may include the creation and publication of blog posts or sharing relevant clinical pearls through YouTube or Twitter, as well as podcasts discussing and debating the most recent literature and evidence-based practice (Cocchio & Awad, 2014). Several studies reported using social media to teach nursing students about online professionalism (Barnable et al, 2018;Englund et al, 2012;Green et al, 2014;Marnocha et al, 2017).…”
mentioning
confidence: 99%
“…Social media can provide students and educators with opportunities to connect with international peers and colleagues and engage in knowledge mobilization (Choo et al, 2014). Such knowledge mobilization activities may include live tweeting at conferences to reach audiences beyond those present in the venue (Cocchio & Awad, 2014).…”
mentioning
confidence: 99%